Introduction to Cloud Computing Fundamental for Teachers and Students of SMK Negeri 1 Karangdadap Kabupaten Pekalongan - Liptia Venica; Muhammad Ayyas; Muchamad Amin Maezun Ta'sin Billah; Rista Dewi Opsantini; Syaifi Al-Mahfudzi (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2023)
The use of cloud computing technology is currently increasingly widespread. The purpose of this community service is to introduce vocational high school students and teachers to cloud computing and implement it to solve computational problems. Participants are introduced to cloud architecture, the advantages of using cloud, various cloud service providers, and different categories of products that the cloud service providers deliver. During the training, participants are provided with the case studies on the use of three products available on Google Cloud Platform (GCP), i.e., Compute Engine, Cloud Storage, and Cloud Vision API. As a result, participants are able to create virtual machines using Compute Engine, publish static web pages using Cloud Storage, and create an application to detect the name and location of a landmark from an image using Cloud Vision API. After this activity, participants are expected to be able to explore other cloud products available and use them to create their own projects.